THE DEVELOPMENT OF BUSY BOOK MEDIA BASED ON THE GLOBAL METHOD ON LEARNING EARLY READING - Yuliyati Irsalina; Rina Yuliana; Trian Pamungkas Alamsyah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aims to determine the steps to develop busy book learning media, the feasibility of busy book learning media products, and students' responses after using busy book learning media based on global methods on learning early reading. This study used Sugiyono R&D development model (2010:409) which has six steps in its development, namely: (1) Analysis of Problems, (2) Data Collection, (3) Product Design, (4) Design Validation, (5) Design Revision, and (6) Product Testing. This research produced a product in the form of Busy Book as a learning media based on the assessment of material from the experts which got a percentage of 86.3% with very feasible category, the assessment of linguists got a percentage of 85% with very feasible category, the assessment of the media experts got a percentage of 90% with very feasible category, and assessment in limited trials got a percentage of 94% with very good category. Based on the results of the study, it can be concluded that the Busy book media based on global methods can be said to be very feasible to use in learning to begin with after going through 6 stages.